To Link or Not to Link: A Network Analysis of Labor - Syahputra, Firdaus Kurniawan (International Journal of Economics Studies, 2025)
This study examines the structure ofstructure of social networks on labor mobility. This study examines the structure of social networks on labor mobility and the factors that cause it, in Mataram and the West Lombok region. Social network analysis (SNA) is used asmethod to achieve the research objectives. By taking a sample of 122 samples randomly. From the results of data processing, it is known that 1.) Labor-Company: Degree Centrality: 1.060, Betweenes: 0.0 Avrge Length:1.0Modularity: 0.796 and Number of Communities: 23. 2.)Labor-Region DegreeCentrailty: 1.542 Betweenes: 0.0 Average Length: 1.0 Modularity: 1.466 and Number of Communities: 23 of Comunitites: 11 And there are 7 motives why labor decides to do mobility. With this we can find outhow the network between regions or companies that become the destination of. And what motives encourage workers to perform mobility.